Lipidomics and whole-genome sequencing identify lipid profiles in fermented golden pompano (Trachinotus ovatus) inoculated with Bacillus subtilis: influence of indigenous strains on lipid changes - Yanyan Wu; Huifang Wang; Huan Xiang; Di Wang; Chunsheng Li; Shengjun Chen; Yongqiang Zhao; Yueqi Wang (Food Science and Human Wellness)
Inoculated fermentation enables rapid fermentation of aquatic products. No studies have been conducted on the lipid profiles of inoculated fermented golden pompano (Trachinotus ovatus). In this study, a lipase-producing Bacillus subtilis with salt tolerance was screened from traditionally fermented golden pompano (TF) and used as a starter culture. Whole-genome sequencing analysis revealed it carries 4 clustered regularly interspaced short vpalindromic repeats structures and 2 genes encoding triacylglycerol lipase. Untargeted lipidomics identified lipid molecules (833) in 6 major classes from B. subtilis SCSMX-2 fermented golden pompano (IF). A total of 28 lipid molecules were upregulated in IF, including phosphatidylcholines (PCs), triacylglycerols (TAGs), and lysophosphatidylcholine. B. subtilis supplementation enhanced the production of polyenyl PCs and medium- and long-chain TAGs. The IF rich in linoleic, docosahexaenoic acids (DHA), and eicosapentaenoic acid were primarily distributed in the sn-2 position of DHA, PC and phosphatidylethanolamine. This research revealed the lipid profiles of IF, providing theoretical basis for the application of B. subtilis in the fermented fish industry.